The Tryptophan Residue at the Active Site Tunnel Entrance of Trichoderma reesei Cellobiohydrolase Cel7A Is Important for Initiation of Degradation of Crystalline Cellulose - Nakamura, Akihiko (American Society for Biochemistry and Molecular Biology, 2013)
The glycoside hydrolase family 7 cellobiohydrolase Cel7A from Trichoderma reesei is one of the best studied cellulases with the ability to degrade highly crystalline cellulose. The catalytic domain and the cellulose-binding domain (CBD) are both necessary for full activity on crystalline substrates. Our previous high-speed atomic force microscopy studies showed that mutation of Trp-40 at the entrance of the catalytic tunnel drastically decreases the ability to degrade crystalline cellulose. Here, we examined the activities of the WT enzyme and mutant W40A (with and without the CBD) for various substrates. Evaluation and comparison of the specific activities of the enzymes (WT, W40A, and the corresponding catalytic subunits (WT(cat) and W40A(cat))) adsorbed on crystalline cellulose indicated that Trp-40 is involved in recruiting individual substrate chains into the active site tunnel to initiate processive hydrolysis. This was supported by molecular dynamics simulation study, i.e. the reducing end glucose unit was effectively loaded into the active site of WT(cat), but not into that of W40A(cat), when the simulation was started from subsite −7. However, when similar simulations were carried out starting from subsite −5, both enzymes held the substrate for 50 ns, indicating that the major difference between WT(cat) and W40A(cat) is the length of the free chain end of the substrate required to allow initiation of processive movements; this also reflects the difference between crystalline and amorphous celluloses. The CBD is important for enhancing the enzyme population on crystalline substrate, but it also decreases the specific activity of the adsorbed enzyme, possibly by attaching the enzyme to non-optimal places on the cellulose surface and/or hindering processive hydrolysis.